Effect of Composition and Thermal Treatments on Mechanical Properties and Applications of Quenching and Partitioning Steels - Michele Maria Tedesco; Daniele De Caro; Paola Rizzi; Marcello Baricco (Metals, 2023)
In this review, we compared nine different chemical compositions and several heat treatments applied on quenching and partitioning steels investigated in the literature. All of these parameters were correlated to the reported mechanical properties (e.g., yield, tensile strength, elongation and toughness). Sustainability and a circular economy approach for applications in the automotive sector were also considered, providing hints for lightweighting in the car industry and the next possible steps to improve the decarbonization of the steel industry.